INCOME STATEMENT ANALYSIS DEPARTMENT OF ROOM TO GOODWAY HOTEL BATAM - Aryati, Yannik (JURNAL DIMENSI, 2012)
Based on the background of the proposed research. A hotel room usually offer a variety of classes and each class is different room rates. Differences in rates due to different facilities provided, so that costs are contained also different.This study aims to determine how to allocate joint costs to each type of room so we can calculate the contribution of each type of room for profit department.This study uses descriptive quantitative study comparing the inter-company data obtained with the various theories that support the discussion in the form of numbers. Based on the results showed that the allocation of shared costs is calculated by using the relative sales value method to obtain the profit contribution for each type of room, superior room which contributes the largest rooms department profit.